Alemtuzumab therapy changes immunoglobulin levels in peripheral blood and CSF - Möhn, Nora (Neurol Neuroimmunol Neuroinflamm, 2019)
OBJECTIVE: The use of alemtuzumab, a humanized monoclonal anti-CD52 antibody has changed the therapy of highly active relapsing-remitting MS (RRMS). Alemtuzumab infusion depletes most lymphocytes in peripheral blood, whereas differential recovery of immune cells, probably those with a less CNS-autoreactive phenotype, is supposed to underlie its long-lasting effects. To determine whether alemtuzumab significantly reduces immunoglobulin levels in blood and CSF of treated patients, we analyzed blood and CSF samples of 38 patients with MS treated with alemtuzumab regarding changes in immunoglobulin levels. METHODS: Blood and CSF samples of patients were collected at the beginning of alemtuzumab treatment and at 12, 24, and 36 months after the first administration of the drug. Specimens were analyzed regarding immunoglobulin concentrations in blood and CSF. RESULTS: We observed significant and dose-dependent reductions of immunoglobulin levels (IgG, IgM, and IgA) in serum and CSF 12 and 24 months following 2 courses of alemtuzumab. Patients with persistent or returning disease activity who were treated with a third course of alemtuzumab exhibited even further decrease in IgG levels compared with matched controls treated twice. Here, alemtuzumab-treated patients with IgG levels below the lower limits of normal were more susceptible to pneumonia, sinusitis, and otitis, whereas upper respiratory tract and urinary tract infections were not associated therewith. CONCLUSIONS: Our results suggest to monitor IgG levels for safety reasons in patients treated with alemtuzumab—in particular when additional treatment courses are required—and to consider preventive action in critical cases. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with RRMS alemtuzumab reduces immunoglobulin levels.